NEEDS ANALYSIS OF EARLY-STAGE READING MATERIALS DEVELOPMENT FOR ELEMENTARY SCHOOL STUDENTS - Aprianti Derlis; Nidya Chandra Muji Utami; Fahrurrozi Fahrurrozi (Jurnal Cakrawala Pendas, 2023)
Early-stage reading competence is an important aspect that primary school students must have to follow other learning at an advanced level. Teaching materials have an essential role in this early reading learning. This research aims to see the need for developing teaching materials, especially in early-stage reading, to complement the Indonesian teaching materials already used in the research school. The teaching materials for early-stage reading are summarized in the Indonesian teaching materials so that causing the content of the early-stage lesson is less intensive to support learning. This research used interviews, document reviews, and needs analysis questionnaires. Respondents and resource persons in this study were the principal, grade 1 and grade 2 teachers of SDN Cigoong 3 Serang City. The results showed that the Indonesian Language Learning Outcomes (CP) in the reading element in Phase A requires students to master the competency of early-stage reading, so teaching materials are needed with the type of printed publication, using the SAS (Structural Analytic Synthetic) starting reading method. Keywords: Early-stage Reading, Teaching Material, Need Analysis